2014
DOI: 10.1016/j.rbmo.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Failure of intrauterine insemination as rescue treatment in low responders with adequate HCG timing with no oocytes retrieved

Abstract: In this retrospective study, the efficiency of carrying out rescue intrauterine insemination (IUI) in low-responder patients undergoing IVF when no oocytes were retrieved after follicular aspiration and when HCG timing was adequate was analysed. A historical control group was used. Over 13 years, women undergoing IVF with failure to obtain oocytes at follicular aspiration underwent rescue IUI if the following criteria were met: adequate HCG timing; one normal tube; motile sperm count after preparation over 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Another multicenter comparative study which analyzed 7176 initiated cycles also suggested that IVF should be pursued for women demonstrating two follicles, while conversion to IUI was recommended for cycles with only one follicle, if sperm and tubal parameters were favorable (3). It was also clearly demonstrated that performing IUI as a rescue treatment provided no advantage over taking no further action when no oocytes were collected during a timed follicular puncture (6). Encountering unexpected premature ovulation at the time of OPU under anesthesia is another challenge for the clinician as well as for the infertile couple; this is a totally different situation with very few treatment alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Another multicenter comparative study which analyzed 7176 initiated cycles also suggested that IVF should be pursued for women demonstrating two follicles, while conversion to IUI was recommended for cycles with only one follicle, if sperm and tubal parameters were favorable (3). It was also clearly demonstrated that performing IUI as a rescue treatment provided no advantage over taking no further action when no oocytes were collected during a timed follicular puncture (6). Encountering unexpected premature ovulation at the time of OPU under anesthesia is another challenge for the clinician as well as for the infertile couple; this is a totally different situation with very few treatment alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Our IUI work-up has been described previously. 3,27,28 The female work-up included at least pelvic examination, blood chemistry, measurement of hormone levels (including AMH levels), HSG, and pelvic ultrasound (US). A laparoscopic study was performed when HSG findings suggested any abnormality (however minor).…”
Section: The Inclusion Criteriamentioning
confidence: 99%
“…It has been reported that in 5–20% of dominant adequately sized follicles, no oocytes are retrieved (Nargund et al., 2001; Coskun et al., 2010; Coskun et al., 2011). Furthermore, poor responders may have an increased rate of impaired folliculogenesis and oocytes may have lower quality (Matorras et al., 2014) (Fig. 3).…”
Section: Recommendationsmentioning
confidence: 99%
“…No oocyte retrieval with high hCG levels could indicate an ectopic pregnancy (Bringer-Deutsch et al., 2010). In cases where OPU failed to recover oocytes and the administration of the medication was adequate, performing a (rescue) IUI is associated with very low pregnancy rates (<7%) and should not be carried out (Matorras et al., 2014). …”
Section: Recommendationsmentioning
confidence: 99%